Intercultural Language Learners: Are You Providing Opportunities for Your Language Learners to Reflect? - Conway, C; Richards, H (New Zealand Association of Language Teachers, 2014)
As you know, the two strands of Knowledge Awareness - language and culture - have equal weighting in the Learning Languages area of the NZ 2007 Curriculum. This was a paradigm shift in the teaching of additional languages, and to support teachers the Ministry of Education published a report (Newton, Yates, Shearn and Nowitski, 2010) that outlined 6 principles for intercultural communicative language teaching (iCLT). Intercultural language learners develop both the language and ability to engage with the foreign culture (Byram, Gribkova and Starkey, 2002) and interact across cultural boundaries. They are able to see the world through the eyes of others, and also, importantly, look at themselves from the outside (Sercu 2005).